Websites Acessíveis e o uso de CMS - Amaral, Marília A.; Cecílio, Ricardo; Ulbricht, Vania R.; Berg, Carlos H.; Dandolini, Gertrudes; Kaminski, Douglas (Cadernos de Informática, 2011)
The use of content management system makes the web implementation more practical, modular and easier maintenance. But many of these environments do not contemplate accessible websites implementations that focus on special needs. This article reports a study that aimed to develop a website for dissemination of the Research Project on Descriptive Geometry for the hearing impaired and visually. The article describes the adjustments and technical aspects involved in using the Joomla CMS to implement the website accessible.